Multiple Auditing Schemes with Integrity and Reliability in Cloud Computing - Sulthana, MS; Samatha, T; Sravani, V; Mahendra, A (International Journal of Computer Sciences and Engineering, 2025)
Many users store their data in the cloud storage and benefit from high quality applications and services from a common group of configurable computing resources like networks, servers, storage, applications, and services, by these users can avoid the load of local data storage and protection. However, the fact that users no longer have physical control of the large size of data makes data reliability protection in Cloud computing a challenging task, especially for users with constrained computing resources. Cloud computing is used by many software industries nowadays, since security is not provided in cloud, many companies adopt their unique security structure. To avoid this problem, users can route data to a third party auditor (TPA) he can check the integrity of rooted data.TPA can be securely introduced such that the auditing process should not create any problems towards user data privacy, and should not bring in no added load to user. In this paper, we are securing the user data and providing privacy. We further expand the TPA to carry out multiple auditing tasks concurrently and powerfully. Wide-range of security and performance investigation shows the proposed schemes are provably secure and highly efficient.